2023
DOI: 10.1186/s12886-023-02910-8
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-prominent cell clusters among human lens epithelial cells: integrated single-cell RNA-sequencing analysis

Abstract: Background Autophagy is an important process that maintains the quality of intracellular proteins and organelles. There is extensive evidence that autophagy has an important role in the lens. Human lens epithelial cells (HLECs) play a key role in the internal homeostasis of the lens. HLEC subtypes have been identified, but autophagy-prominent cell clusters among HLECs have not been characterized. Purpose To explore the existence of autophagy-promin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…While recent studies have reported single-cell RNA-seq analysis of the lens in zebrafish 52 , mouse 53 , and human [93][94][95] , there remains a need to apply single-cell multiomic outlooks to comprehensively examine lens development. The present work encompasses a comprehensive multiomic analysis of the embryonic chicken lens at single-cell resolution, which portrays a novel, holistic perspective of epithelial to fiber cell differentiation and the associated gene regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…While recent studies have reported single-cell RNA-seq analysis of the lens in zebrafish 52 , mouse 53 , and human [93][94][95] , there remains a need to apply single-cell multiomic outlooks to comprehensively examine lens development. The present work encompasses a comprehensive multiomic analysis of the embryonic chicken lens at single-cell resolution, which portrays a novel, holistic perspective of epithelial to fiber cell differentiation and the associated gene regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 In order to characterize the different LEC transcriptional states and to probe potential subpopulations that underscore this critical proliferative event, we utilized single-cell RNA sequencing (scRNA-seq) technology. Previous single-cell RNA sequencing studies in the lens have been conducted in zebrafish, 15 , 16 human, 17 19 Drosophila , 20 chick, 21 and adult murine lenses. 22 However, the early postnatal mouse lens epithelium has not yet been characterized using this method.…”
mentioning
confidence: 99%